(untitled) (Journal of Social Sciences Review, 2022)
In this research study, the main purpose was to evaluate the job performance of physical education teachers (PETs) who were working at the university level in Pakistan. The current research was designed through a cross-sectional survey from the descriptive model. The total population of the study was 10370. The researcher used a cluster sampling technique to choose the sample. The 10% research sample consisted of n=1037 (HODs= 6; physical education students= 1031). As the data collection tool, an adapted scale developed by the National Association for Sports and Physical Education (NASPE) was used for the performance evaluation of PETs. Descriptive Statistics (mean, standard deviation, frequency percentage, minimum, maximum, and variance) were used to assess the data. In order to compare the quantitative data, an independent sample t-test was used. The hypotheses were tested with a 95% confidence interval and .05 significant levels. The findings of the study revealed that the majority of HODs were quite satisfied with the job performance of PETs; however, students’ responses were stated lesser than the HODs. As a result, it was recommended that the evaluation of the job performance of PETs should be conducted through a multiple inspection committee. For this purpose, HODs, Quality Enhancement Cells (QEC) and student’s parents may be included.